Hypothalamic Control of Glucose Homeostasis and Diabetes - Vinall, Maria (MD Conference Express, 2014)
Research by the French physiologist Claude Bernard more than a century ago established the connection between the brain and the control of glucose levels, the main mechanism of glucose homeostasis and energy balance. Beginning with Professor Bernard’s groundbreaking findings, This article discusses the history of hypothalamic research including his own current work on the impact of the hypothalamus on diabetes.